Effect of antiretroviral therapy on the mortality of HIV-1 infection long-term non-progressors: a cohort study - Jinming Su; Jie Liu; Fengxiang Qin; Rongfeng Chen; Tongxue Qin; Xing Tao; Xiu Chen; Wen Hong; Bingyu Liang; Ping Cui; Li Ye; Junjun Jiang; et al. (BMC Infectious Diseases)
Abstract Background The study aims to investigate the demographic characteristics, the variations in their immune status, and mortality risk among HIV-1 infection long-term non-progressors (LTNP). Methods Eligible LTNP and typical progressors (TP) were recruited in Guangxi by December 2018. Participants were followed up until December 2022, monitoring ART status, CD4+ T cell counts, and survival/death outcomes. Multivariate logistic, Cox regression, and Kaplan-Meier method were employed to scrutinize associated factors and mortality risk of LTNP. Results A total of 212 LTNP and 390 TP were included. LTNP cohort predominantly comprised males (84.43%), those diagnosed with HIV at age ≤ 40 years (93.87%), and those infected through injection drug use (59.91%). The mortality rate of LTNP were lower than TP (12.74% vs. 27.18%). TP had a higher mortality risk compared to LTNP (adjusted hazard ratio [aHR] = 4.051, 95% CI: 2.284–7.186, P < 0.001). The mortality risk was also elevated in the ART-naïve group versus the ART-experienced ones (aHR = 3.943, 95%CI: 2.658–5.850, P < 0.001). Notably, the CD4/CD8 ratio in the LTNP group did not fully recover (< 1.0) despite ART. However, LTNP with ART-experienced had a significantly lower mortality risk compared to ART-naïve LTNP group (Log-rank: P = 0.003). Conclusions ART effectively restores and maintains normal CD4+ T cell levels among LTNP, thereby decreasing mortality risk. Nonetheless, the CD4/CD8 ratio in LTNP exhibits incompletely recovered post-ART. These findings provide a scientific foundation for promoting ART in LTNP population.